Identifikasi Gen Pap C Dan Fim A Pada Bakteri Escherichia Coli Penghasil ESBL Sebagai Faktor Adhesi Pada Infeksi Saluran Kemih - Anang Kurniawan; Ade Hasan Basri; Ary Nahdiyani Amalia; Fibrinika Tuta Setiani; Indrawati Aris Tyarini; Nazilla Nugraheni (Media Informasi Penelitian Kabupaten Semarang, 2023)
Problem: UTI (urinary tract infection) is an infection caused by bacterial invasion of the urinary tract. Escherichia coli bacteria is a strain that often causes UTIs (urinary tract infections). This bacterium has the ability to attach or attach to the host epithelium as a condition for disease formation, one of these factors is due to the expression of fimbriae. Purpose: the aim of this study was to identify the PapC and fim A genes in esble-producing e.coli bacteria as adhesion factors in urinary tract infections. Methods: This study was included in a cross-sectional study conducted for 3 months. E. coli isolates were obtained from urine samples of UTI patients who were hospitalized. To detect ESBL-producing E.coli strains, HiCromeTM ESBL Agar Base (Himedia) was used and PCR was used to detect PapC and FimA genes. Results: From 40 samples obtained for 3 months, 10 isolates of ESBl-producing E. coli were obtained and the PapC and FimA genes identified from the PapC and FimA genes were identified. showed that 8 samples were positive for Pap C (80%) (figure 2) and Fim A gene 10 (100%).